The Role of Sociodemographics in Moderating the Influence of Financial Literacy and Financial Knowledge on Financial Freedom - Pratiwi Dewanto, Sekar Errianda; Sampurna, Dian Surya (Green Publisher Indonesia, 2026)
The purpose of this study is to examine the influence of tax planning, corporate governance, and financial performance on manufacturing companies in the real estate and property sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2018 – 2020. This study uses a type of quantitative research with a descriptive research strategy. The population of this study is 65 companies in the real estate and property sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2018 – 2020. The sample selection in this study used purposive sampling with a sample of 42 companies so that there were 126 total observations. The data used is secondary data. Data collection techniques through the official IDX website: www.idx.co.id and the company's official website. This study uses Eviews software version 10. The results of the study prove that, (1) Tax Planning has no effect on Company Value, (2) Managerial Ownership has no effect on Company Value, (3) Institutional Ownership has a significant positive effect on Company Value, (4) Independent Commissioners have a significant positive effect on Company Value, (5) Audit Committee has a significant positive effect on Company Value, (6) Capital Structure has a significant negative effect on Company Value, (7) Profitability has a significant positive effect on Company Value, (8) Liquidity has a significant positive effect on Company Value.